Bridging the training–practice gap in social-emotional learning of pre-service teachers - Duc-Hoi Dinh; Thien-Vu Giang; Van-Son Huynh (Institute of Advanced Engineering and Science, 2026)
To successfully embed the social-emotionallearning (SEL) model in the education sector, pre-service teachers must prepare for social-emotional competence (SEC). Unfortunately, studies on how pre-service teachers were trained and developed their SEC before practicing the SEL model in the teaching profession are lacking. This study focuses on discovering how to train and develop SEC for pre-service teachers within the framework of teacher undergraduate training programs in Vietnam, a developing country in Southeast Asia. We employed a convergent parallel mixed-method approach, utilizing both quantitative data (n=650) and qualitative data (n=23), which were subsequently integrated during the interpretation phase to derive comprehensive results. Our findings revealed that the current pre-service teachers had an average level of SEC, which was limited by: i) confusion in understanding SEC and SEL concepts; ii) the lack of professional supervision in undergraduate training; and iii) the unguaranteed need to foster SEC self-development and SEL-based practice training courses. These themes highlight the need to change the administrative policy in undergraduate teacher training programs to support and supervise the development of pre-service teachers’ SEL-based knowledge and practice in developing countries.